2017
DOI: 10.1111/ajt.14138
|View full text |Cite
|
Sign up to set email alerts
|

Telemedically Supported Case Management of Living-Donor Renal Transplant Recipients to Optimize Routine Evidence-Based Aftercare: A Single-Center Randomized Controlled Trial

Abstract: Improving mid-term and long-term outcomes after solid organ transplantation is imperative, and requires both state-of-the-art transplant surgery and optimization of routine, evidence-based aftercare. This randomized, controlled trial assessed the effectiveness of standard aftercare versus telemedically supported case management, an innovative aftercare model, in 46 living-donor renal transplant recipients during the first posttransplant year. The model includes three components: (i) chronic care case managemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
93
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(95 citation statements)
references
References 28 publications
2
93
0
Order By: Relevance
“…Studies were conducted in liver (n = 8), kidney (n = 25), heart or heart/lung (n = 2), and lung transplant recipients (n = 4), as well as mixed groups (n = 2). Of the RCTs, 11 did not report on transplant outcomes, and 10 examined them and found no effect of the intervention . Table is a detailed review of the 10 RCTs that looked at transplant outcomes (and found no intervention effect); this table also presents other outcomes that were examined in those studies.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies were conducted in liver (n = 8), kidney (n = 25), heart or heart/lung (n = 2), and lung transplant recipients (n = 4), as well as mixed groups (n = 2). Of the RCTs, 11 did not report on transplant outcomes, and 10 examined them and found no effect of the intervention . Table is a detailed review of the 10 RCTs that looked at transplant outcomes (and found no intervention effect); this table also presents other outcomes that were examined in those studies.…”
Section: Resultsmentioning
confidence: 99%
“…Intervention strategies that are likely to improve transplant outcomes in non‐adherent patients probably have to be more comprehensive than simple reminders or automated strategies, yet also unobtrusive enough to avoid posing an excessive burden on patients. A promising example involves the use of intensive case management delivered via a telemedicine paradigm …”
Section: Discussionmentioning
confidence: 99%
“…length of unplanned hospital stay compared to those in the standard care group. 13 This study has several limitations. First, given that this was a secondary analysis of existing data, it is unclear whether the presence of other factors not assessed in this study confounded the significant association between multidisciplinarity and level of CIM.…”
Section: Discussionmentioning
confidence: 92%
“…12 In transplantation, the reengineering of transplant follow-up care according to the principles of CIM has resulted in improved clinical outcomes, reduced health care utilization, and reduced costs. 10,13 In the most recent guidelines for the care of HTx recipients, the International Society of Heart and Lung Transplantation (ISHLT) recommended that transplant centers utilize a multidisciplinary approach to patient management. 6 This recommendation is similar to the Centers for Medicare and Medicaid policy that specifies that a multidisciplinary team should be involved in the care of transplant recipients throughout all phases of the transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…Convincing evidence from other chronic illnesses like heart failure or diabetes shows that better management results in improved outcomes . Two renal transplant programs found better adherence and fewer emergency visits and hospital readmissions in patients exposed to a transplant follow‐up model based on the principles of chronic illness management …”
mentioning
confidence: 99%